1976
DOI: 10.1007/bf00011373
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of environmental stress on seed yield of cowpea (Vigna unguiculata (L.) walp.) cv. Prima

Abstract: Separate experiments examined nodulation and seed yield of cowpea cv. Prima after (a) changes in the level of combined nitrogen from 25 to 0 or 60 ppm N, (b) cycles of wilting and rehydration, and (c) shading to ca 50% full daylight. Plants were grown ill the simulated tropical environment of a plastics 'bubble' house and experienced these changes over the growth stages: emergence to first flower, first flower to mid pod-fill or mid pod-fill to maturity.Seed yields of nodulated plants were unaffected by combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 12 publications
4
23
1
1
Order By: Relevance
“…From the obtained data, moisture stress at vegetative stage significantly reduced branch production in this study. This is in line with the work of Mustapha et al (2014) who found that water stress reduced branching in selected soya bean genotypes; and Summerfield et al (1976) who reported that water-stressed cowpea plants were reduced in branching. Reduction in the number of secondary buds can be a phenomenon by the plants to decrease surface area over which transpiration takes place.…”
Section: Effect Of Water Stress On Growth Parameters Of Nightshades Nsupporting
confidence: 92%
“…From the obtained data, moisture stress at vegetative stage significantly reduced branch production in this study. This is in line with the work of Mustapha et al (2014) who found that water stress reduced branching in selected soya bean genotypes; and Summerfield et al (1976) who reported that water-stressed cowpea plants were reduced in branching. Reduction in the number of secondary buds can be a phenomenon by the plants to decrease surface area over which transpiration takes place.…”
Section: Effect Of Water Stress On Growth Parameters Of Nightshades Nsupporting
confidence: 92%
“…Biscoe & Gallagher (1977) have reviewed this topic. Shading experiments with cowpea reduced seed yield by reducing number of pods though there was a slight increase in mean pod weight (Summerfield et al 1976).…”
Section: Discussionmentioning
confidence: 94%
“…The few studies that measured cowpea NA when water was limiting showed that NA was depressed during periods of water deficit (Summerfield et al 1976;Wien et a\. 1979) In a greenhouse study, Summerfield et al (1916), showed that cowpea NA was unable to recover from drought stress imposed at preflowering stages.…”
mentioning
confidence: 99%